The James Clerk Maxwell Telescope Legacy Survey of Nearby Star-forming Regions in the Gould Belt - Ward-Thompson, D; Francesco, J; Hatchell, J; Hogerheijde, MR; Bastien, P; Basu, S; Bonnell, I; Bowey, J; Brunt, C; Buckle, J; Butner, H; Cavanagh, B; et al. (2007)
This paper describes a James Clerk Maxwell Telescope (JCMT) legacy survey that has been awarded roughly 500 hrs of observing time to be carried out from 2007 to 2009. In this survey we will map with SCUBA-2 (Submillimetre Common User Bolometer Array 2) almost all of the well-known low-mass and intermediate-mass star-forming regions within 0.5 kpc that are accessible from the JCMT. Most of these locations are associated with the Gould Belt. From these observations we will produce a flux-limited snapshot of star formation near the Sun, providing a legacy of images, as well as point-source and extended-source catalogues, over almost 700 square degrees of sky. The resulting images will yield the first catalogue of prestellar and protostellar sources selected by submillimetre continuum emission, and should increase the number of known sources by more than an order of magnitude. We will also obtain CO maps with the array receiver HARP (Heterodyne Array Receiver Programme), in three CO isotopologues, of a large typical sample of prestellar and protostellar sources. We will then map the brightest hundred sources with the SCUBA-2 polarimeter (POL-2), producing the first statistically significant set of polarization maps in the submillimetre. The images and source catalogues will be a powerful reference set for astronomers, providing a detailed legacy archive for future telescopes, including ALMA, Herschel and JWST.